2002
DOI: 10.1080/02652040110055207
|View full text |Cite
|
Sign up to set email alerts
|

α-Tocopherol encapsulation and in vitro release from wheat gliadin nanoparticles

Abstract: Alpha-tocopherol, or vitamin E (VE), is widely used as a strong antioxidant in many medical and cosmetic applications, but is rapidly degraded, because of its light, heat and oxygen sensitivity. Thus, all of its formulation has to avoid contact with light, heat or air. Drug loaded carriers are an attractive opportunity, especially if they are made for bioacceptable macromolecules such as vegetal proteins. For instance, gliadins, extracted from wheat gluten, generate nanoparticles by a desolvatation method and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(26 citation statements)
references
References 13 publications
1
24
1
Order By: Relevance
“…This type of constant decrease in encapsulation efficiency of active ingredient was also observed in another independent study where hydrophobic nutraceutical ingredient (vitamin E) was encapsulated in wheat gliadin nanoparticles. It was found that 900.0 nm sized nanoencapsulated vitamin E particles were formed with encapsulation efficiency of 95-77 % in increasing order of vitamin E concentration relative to gliadin weight (Duclairoir et al 2002). The decrease in fraction of spontaneously forming cavities of nanoassemblies to the added curcumin amount could be the reason behind aggregation of the nanoparticles and precipitation of curcumin beyond this concentration.…”
Section: Encapsulation Efficiency (Ee) and Curcumin Loading (Cl)mentioning
confidence: 97%
“…This type of constant decrease in encapsulation efficiency of active ingredient was also observed in another independent study where hydrophobic nutraceutical ingredient (vitamin E) was encapsulated in wheat gliadin nanoparticles. It was found that 900.0 nm sized nanoencapsulated vitamin E particles were formed with encapsulation efficiency of 95-77 % in increasing order of vitamin E concentration relative to gliadin weight (Duclairoir et al 2002). The decrease in fraction of spontaneously forming cavities of nanoassemblies to the added curcumin amount could be the reason behind aggregation of the nanoparticles and precipitation of curcumin beyond this concentration.…”
Section: Encapsulation Efficiency (Ee) and Curcumin Loading (Cl)mentioning
confidence: 97%
“…The method to determine the loading efficiency of VE was referenced from 21 . About 1 mg of chitosan-coated liposomes was digested in 10 ml of the ethanol/water mixture at 25 C in the dark.…”
Section: Ve Loading Efficiencymentioning
confidence: 99%
“…The phenolic hydroxyl group of vitamin E donates hydrogen atoms, acting as a membrane stabilizing agent and free radical scavenger which can prevent the peroxidation of the polyunsaturated fatty acyl chains of membrane lipids [20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…The use of nanoparticles besides improving solubility in water, also provides controlled releasing. Some materials such as gliadin nanoparticles [5] , self-assembled nanoparticles of tocopheryl monoesters modified-chitosan conjugates [6] , and chitosan nanoparticles coated with zein [7] have been reported.…”
Section: Introductionmentioning
confidence: 99%